Sibling Rivalry pada Anak Usia Dini - Ainnunnisa, Ridha; Rachmawati, Yeni (Universitas PGRI Semarang, 2024)
AbstractSibling rivalry is a common issue observed among children with their siblings. It arises from competition and jealousy between siblings. In its management, parents must possess knowledge and strategies regarding cases of sibling rivalry. This research aims to delve into sibling rivalry, encompassing the causative factors and the consequences of sibling rivalry that occur in early childhood. This study also hopes to illustrate the efforts of parents in addressing the occurrence of sibling rivalry in young children. The research method employed in this study is qualitative through systematic review, by collecting several previous studies on sibling rivalry, then organizing and analyzing relevant research. The results of the review from this research reveal that the occurrence of sibling rivalry in early childhood is influenced by several factors, namely the age gap between siblings, parenting styles, and the number of siblings. Sibling rivalry can impact the children themselves as well as their siblings, leading to physical and psychological aggression towards each other. Therefore, efforts that parents can undertake in managing sibling rivalry include enhancing their knowledge, setting an example for their children, implementing parenting practices that benefit all children, and encouraging children to engage in activities that foster cooperative, healthy competition, and a willingness to collaborate in various endeavors.Keywords: Early childhood; sibling rivalry; parentsAbstrakSibling rivalry merupakan sebuah kasus yang sering dikunjungi pada anak dengan saudara kandungnya. Hal ini terjadi akibat persaingan dan kecemburuan antar saudara kandung. Dalam penanganannya orang tua harus memiliki pengetahuan dan strategi mengenai kasus sibling rivalry. Penelitian ini bertujuan untuk mendalami mengenai sibling rivalry, yang berisikan faktor penyebab serta dampak sibling rivalry yang terjadi pada anak usia dini. Penelitian ini diharapkan juga dapat menggambarkan upaya orang tua untuk menangani terjadinya sibling rivalry pada anak usia dini. Metode yang digunakan dalam penelitian ini adalah metode kualitatif melalui literature review, dengan mengumpulkan beberapa penelitian sebelumnya mengenai sibling rivalry, selanjutnya penelitian yang relevan disusun dan dianalisis. Hasil review dari penelitian ini dapat diketahui bahwa terjadinya sibling rivalry pada anak usia dini didasari dari beberapa faktor yaitu jarak usia antar anak, pola asuh, dan jumlah saudara. Sibling rivalry akan berdampak pada diri anak sendiri maupun saudaranya seperti saling melakukan kekerasan fisik maupun psikis. Oleh sebab itu, upaya yang dapat dilakukan oleh orang tua dalam menangani sibling rivalry dengan meningkatkan pengetahuan, menjadi tauladan bagi anak, pola asuh yang diterapkan menguntungkan semua anak, serta mengajak anak untuk melakukan kegiatan yang meningkatkan sikap kooperatif, kompetitif, dan minat bekerjasama dalam berbagai aktivitas.Kata kunci: Anak usia dini; sibling rivalry; orang tuaÂ